2016
DOI: 10.4067/s0718-27242016000200006
|View full text |Cite
|
Sign up to set email alerts
|

SMEs' Innovation and Export Capabilities: Identification and Characterization of a Common Space Using Data Spatialization

Abstract: Numerous publications try to identify and test empirically the link between innovation and export to explain firms' competitiveness. But it seems that several ways of thinking coexist, without a real consensus. This article proposes a different approach, by considering innovation and export not in terms of impact of the one on the other, but rather as two complementary activities mobilizing common capabilities (resources, skills, knowledge). These common capabilities represent the capabilities that a company n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
1
15
0
3
Order By: Relevance
“…However, the results achieved in Model 2 are not conclusive. As already mentioned in Model 1, the variable XS shows a positive sign suggesting that trade liberalisation positively impact the development of technology capacity (TCI) through competition given that this effect improves firms' absorptive capacity for acquiring new technologies from abroad (Enjolras et al, 2016;Erdal and Göçer, 2015). As expected, Hypothesis 5 aims to capture the idea that innovation developments contribute to explain technology advances in the manufacturing sector of Mexico.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…However, the results achieved in Model 2 are not conclusive. As already mentioned in Model 1, the variable XS shows a positive sign suggesting that trade liberalisation positively impact the development of technology capacity (TCI) through competition given that this effect improves firms' absorptive capacity for acquiring new technologies from abroad (Enjolras et al, 2016;Erdal and Göçer, 2015). As expected, Hypothesis 5 aims to capture the idea that innovation developments contribute to explain technology advances in the manufacturing sector of Mexico.…”
Section: Resultsmentioning
confidence: 63%
“…Hypothesis 2 in Model 1 (and Model 2) suggests that the diffusion of new technologies increases exports competitiveness and thus the development of technology capabilities in the manufacturing sector of Mexico (Enjolras et al, 2016;Erdal and Göçer, 2015). In this case, the variable XS is positive and significant, and thus the null hypothesis (β 2 = 0) can be rejected (t-statistic = 5.91).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is confirmed that there is a positive influence of export activities of companies in this respect. Though, conditional on survival, the export growth of companies is negatively associated with the quality of the country's institutions, Enjolras et al (2016) research the way of influence of SMEs' innovation on their export capabilities. Based on received data, they identify several common practices between innovation and export processes, namely: network management, consideration of the customer, the acquisition of information, skills management, the capitalization of knowledge, the global strategy, the follow-up of the projects, the intellectual property, and the corporate culture.…”
Section: Trade and Multinationals Theorymentioning
confidence: 99%
“…Esto es particularmente significativo para el caso de las pequeñas y medianas empresas (Pymes), cuyo acceso a las TI está más limitado que para las grandes empresas debido a sus restricciones de recursos (Mortenson & Vidgen, 2016;Muñoz & Pitti, 2016). De hecho, estudios muestran que las Pymes tienen dificultades para movilizar los recursos necesarios para hacer innovaciones (Enjolras, Camargo & Schmitt, 2016). Este es un problema relevante para las naciones, especialmente las latinoamericanas, porque es sabido el gran aporte que este tipo de empresas realiza a las economías nacionales en términos de contratación de trabajadores (Correa &Echavarría, 2013;Mora et al, 2012;Alves, Salvani, Bansi, Neto & Galiba, 2016).…”
Section: Introductionunclassified